2016
DOI: 10.1007/s00482-016-0180-z
|View full text |Cite
|
Sign up to set email alerts
|

PKT – der Palliative Kompetenztest für Ärzte

Abstract: The PKT is a German questionnaire that was validated to assess the efficiency of palliative education for physicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
1
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 16 publications
1
1
0
5
Order By: Relevance
“…In this study, a higher level of palliative care knowledge was found among physicians who were younger, with longer professional practice and palliative care work experience, and those who participated in continuous training. These results are in agreement with those of Mosich et al (2017), where physicians with undergraduate palliative education and work experience were associated with higher scores in palliative knowledge [ 37 ]. Surprisingly, younger physicians showed greater knowledge.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, a higher level of palliative care knowledge was found among physicians who were younger, with longer professional practice and palliative care work experience, and those who participated in continuous training. These results are in agreement with those of Mosich et al (2017), where physicians with undergraduate palliative education and work experience were associated with higher scores in palliative knowledge [ 37 ]. Surprisingly, younger physicians showed greater knowledge.…”
Section: Discussionsupporting
confidence: 93%
“…Aus diesem Grund erfolgte mithilfe einer Expertengruppe die Entwicklung und anschließende Validierung des Paramedic Palliative Care Test (PARPACT). Als Vorbild bei der Entwicklung des Paramedic Palliative Care Test (PARPACT) dienten der Bonner Palliativwissenstest (BPW; [18]) und der Palliativkompetenztest für Ärzte (PKT; [16] Es ergibt sich eine signifikante statistische Korrelation zwischen der etablierten allgemeinen Selbstwirksamkeitserwartungsskala nach Schwarzer und Jerusalem und der palliativen Selbstwirksamkeitserwartungsskala. Der Spearman-Korrelationskoeffizient beider Skalen liegt bei r = 0,39, p < 0,001.…”
Section: Hintergrundunclassified
“…Aus diesem Grund erfolgte mithilfe einer Expertengruppe die Entwicklung und anschließende Validierung des Paramedic Palliative Care Test (PARPACT). Als Vorbild bei der Entwicklung des Paramedic Palliative Care Test (PARPACT) dienten der Bonner Palliativwissenstest (BPW; [ 18 ]) und der Palliativkompetenztest für Ärzte (PKT; [ 16 ]). Beide Tests beinhalten Items zur palliativen Wissensabfrage sowie zur spezifisch palliativen Selbstwirksamkeitserwartung und wurden vorwiegend zur Evaluation von Bildungsmaßnahmen entwickelt.…”
Section: Hintergrundunclassified
“…Jedoch stellte sich heraus, dass diese aktuell lediglich individuell als Mitarbeitergespräche durchgeführt werden. Eine einheitliche Abfrage von dem durch die Rotation gegebenen Erwerb von Haltung und Handlungswissen bei Ärzten [27,33] oder Gesundheits-und Krankenpflegern [34] wird aktuell an den CCC nicht durchgeführt. Wünschenswert ist hier eine strukturierte Evaluation in den Blick zu nehmen.…”
Section: Rotationsprogrammeunclassified